A novel extraction method of prymnesins from Prymnesium parvum whole culture samples and re-evaluation of existing protocols - Magdalena Pöchhacker; Alexander Conrad; Doris Marko; Elisabeth Varga (Ecotoxicology and Environmental Safety)
Harmful algal blooms caused by Prymnesium parvum can result in massive fish kills. The ichthyotoxins suspected to be responsible, known as prymnesins (PRMs), produced by P. parvum are classified into A-, B-, and C-types. In 2022, a severe HAB event within the Odra/Oder River impacted the environment via these toxins. The detection of PRMs is still a challenge due to a lack of analytical standards and stability issues along with losses during conventional extraction methods. In this study, PRM recovery was assessed for the three most common extraction methods for microalgae, solid-phase extraction (SPE), solid-liquid extraction (SLE), and liquid-liquid extraction (LLE). Furthermore, the impacts from sonication, freezing, and different solvents upon PRM stability were evaluated. Within methanol (MeOH), PRMs remained stable but within aqueous solvents, PRMs degraded rapidly. A novel 50 % MeOH SPE approach was developed, which outperformed LLE and SLE. This method offers advantages for salty whole culture samples through desalination and reduces PRM losses by the omission of reconstitution and evaporation steps. Ethanol as greener alternative to MeOH resulted in lower PRM yields compared to MeOH but showed similar recovery to LLE and still had advantages, besides the ecological ones, like faster and easier handling. The method's robustness was confirmed across all algal growth stages and for all PRM classes, including 6, 4 and 3 analogs for A-, B-, and C-types, respectively. The optimized SPE approach provides a faster, cleaner and more reliable extraction method for PRMs and improves analytical workflows for both natural and laboratory samples.